Scientific Story Writing Technique in the Alternative Assessment of the Subject of Liquids: The Sample of Science and Biology Teaching Students - Gamze Dolu; Handan Ürek; Ayberk Bostan Sarıoğlan (Journal of Science Learning, 2022)
The present study aims to investigate university students’ conceptions of liquids with the help of the scientific story writing technique, which is one of the alternative assessment techniques. The study group comprised students studying science (n=50) and biology teaching departments (n=20) in Turkey. Thus, the study carries within two groups. In both groups, computer-supported teaching was carried out by the same researcher for two weeks regarding the subject of liquids. After this process, a scientific story writing technique applies to collect study data. In data analysis, utilized content analysis and descriptive statistics. Firstly, determined the statements involved in students’ stories. Afterward, ordered the statements under the categories ‘scientifically acceptable’, ‘partially acceptable,’ ‘scientifically unacceptable,’ and ‘not coded.’  The findings showed that the category with the highest percentage in the stories of both groups was the scientifically acceptable category. This result indicated that most of the students figured out the subject. However, I encountered several misconceptions also in students’ statements. Therefore, enrichment of learning methods is needed to eliminate student misunderstandings detected in learning.